2001
DOI: 10.1159/000056034
|View full text |Cite
|
Sign up to set email alerts
|

Occipital Dermal Sinuses

Abstract: Occipital dermal sinuses (ODS) are rare dysraphic lesions resulting from defective separation of the ectoderm and neuroderm. These lesions are often diagnosed at birth and should be treated early because of potentially life-threatening complications. However, the pathogenesis of these rare lesions is still poorly understood, and there is no consensus about the optimal timing of surgery. We reviewed 9 pediatric cases of ODS operated in our department since 1982 and 79 other cases published in the literature dur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(3 citation statements)
references
References 10 publications
1
2
0
Order By: Relevance
“…Groen and van Ouwerkerk [16] observed a genetic determination on a pair of twins, one with CDT and the other with occipital meningocele, and suggested that CDT and meningomyelocele originate from the same pathology, an adhesion between the ectoderm and neuroderm. The probability of genetic factors is also reported by Vinchon et al [7]. …”
Section: Discussionsupporting
confidence: 62%
See 2 more Smart Citations
“…Groen and van Ouwerkerk [16] observed a genetic determination on a pair of twins, one with CDT and the other with occipital meningocele, and suggested that CDT and meningomyelocele originate from the same pathology, an adhesion between the ectoderm and neuroderm. The probability of genetic factors is also reported by Vinchon et al [7]. …”
Section: Discussionsupporting
confidence: 62%
“…The defective cleavage between the ectoderm and the neuroderm during the 3rd to 5th gestational week is responsible for the pathogenesis. However, due to the fact that it is an uncommon disease, the pathophysiology of CDT is not well defined [7]. The tumor generally sits on the midline of the posterior fossa, vermis, and spine, which are on the closing line of the neural tube [6].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation